Penerapan Metode Curah Gagasan (Brainstorming) Untuk Meningkatkan Kemampuan Mengemukakan Pendapat Siswa - Diyah Amin (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
Based on the observations made by researchers, there are four problems that occur in the classroom are: less of enthusiasm of the students in following the teaching of history, less of response to the student when giving responses and rebuttals, students are less active to ask and answer questions of teachers and teaching is also still using the approach teacher center. The method used is a method of classroom action research with four cycles. This classroom action research conducted in Man Cirebon 1 in class XI IPS 4. In the first cycle students have not implemented the method brainstorming well but, after investigator learned from the first cycle, the teacher gave them the motivation to reward, and the media that interest the students. The result in the second cycle, third and fourth categories of students’ ability to express opinions is at a good level. because students are enthusiastic in identifying questions, looking for ideas or ideas, find an idea or ideas, formulate opinions and submit an opinion in the teaching of history.Keywords: brainstorming, express opinions, and reward